Improvement of Care Cascade for Hypertension and Diabetes in Rural China: Protocol for an Implementation Study - Xuejun Yin; Zhenzhong Wang; Jingsong Yang; Jia Li; Shasha Han; Wenshuai Feng; Qinglan Liu; Ning Li; Lihui Zhang; Jiawen Ke; Xiaoxia Wei; Juan Zhang; et al. (The Journal of Clinical Hypertension)
ABSTRACT The management of hypertension and diabetes poses significant challenges to China's healthcare system, necessitating seamless patient progression through screening, diagnosis, management, and control. Utilizing the care cascade model, this study aims to systematically identify patient drop‐offs and devise strategies to address healthcare delivery bottlenecks for hypertension and diabetes in rural China. This study consists of three phases. In Phase 1, qualitative interviews are conducted to explore healthcare experiences and identify determinants across the care cascade. Phase 2 involves systematically assessing barriers identified in Phase 1 and collaborating with local stakeholders using intervention mapping and co‐design to generate interventions and implementation strategies. Phase 3 is a cluster randomized controlled trial involving 48 villages, randomly assigned in a 1:1 ratio, to compare changes in hypertension and diabetes care. Intervention villages will implement interventions developed in Phase 2 for 1 year, while control villages will continue with usual care. Primary outcomes include between‐group differences in achieving blood pressure and glycemic targets, along with service and implementation outcomes. This study aims to identify the stage with the largest patient retention gap in the care cascade and develop intervention strategies through participatory co‐design with practitioners, emphasizing feasible, low‐cost approaches. The pragmatic cluster RCT will assess strategy effectiveness, offering valuable insights for practical interventions to enhance hypertension and diabetes care in rural settings, potentially shaping impactful programs and improving healthcare outcomes. Trial Registration: ClinicalTrials.gov. identifier: NCT06141278